Pengaruh Reputasi Underwriter, Reputasi Auditor, Ukuran Perusahaan, Dan Umur Perusahaan Terhadap Tingkat Underpricing Saham Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2021 - Febriyanto, Febriyanto; Septiana, Nani; Turohman, Nurhidayat (Universitas Muhammadiyah Metro, 2023)
This study aims to test and analyze the influence of underwriter's reputation, auditory,company size, and the company's age against underpricing levels. This research wasconducted by purposive sampling method with a sample of 133 companies that carried outinitial public off catering (IPO) in a vulnerable period of 2019 - 2021. The data used issecondary data through the annual company report in 2019-2021. The data analysis used inthis study was the Liniear Multiplication analysis. The results of this study indicate that thecompany's reputation, and the company's age did not significantly affect the underpricinglevel. While the reputation of auditors, negative affects underpricing level. And company size,positively affect the underpricing level. underwriter's reputation, auditory reputation,company size, and corporate life together (simultaneous) affect and significant tounderpricing's level. The advice that can be given based on the results of this study are forfurther research are advised to use more consistent, clear measuring tools for underwriter'sreputation measurements and auditory reputation reputation reputations. Inconsistency cancause inconsistent results in the research conducted. In addition, further research can useother variables that can potentially affect the underpricing level of shares in the company.